Our experience in a psychodermatology liaison clinic at Manipal, India - Shrutakirthi D Shenoi; Smitha Prabhu; B Nirmal; Shailee Petrolwala (Wolters Kluwer Medknow Publications, 2013)
Psychodermatology is an emerging specialty in dermatology which deals with the interactions between mind and skin. Psychocutaneous diseases can be either primary psychiatric or primary cutaneous, with various degrees of associations between psyche and skin. Unless the dermatologist cultivates a special interest in this field, many an invisible mental disorder may be missed leading to sub optimal treatment of the visible skin condition. Though Dermatology Psychiatry liaison clinics are common in Europe and other western countries, it is just an emerging concept in India.Here we describe the working pattern of psychodermatology liaison clinic established in Manipal in August 2010 and describe briefly the type of cases attended to.